Direct-acting antiviral hepatitis C virus treatment perturbation of the metabolic milieu. Issue 2 (February 2019) - Driedger, Matt; Galanakis, Chrissi; Doyle, Mary-Anne; Cooper, Curtis L.
Abstract : Objective: Hepatitis C virus (HCV), cirrhosis, and HCV medications including direct-acting antivirals (DAAs) ±ribavirin may all influence the metabolic milieu. While interferon-based regimens improve glucose tolerance, evidence is limited on DAAs. Cases of elevated lactate have recently been reported in patients treated with DAAs, and lactic acidosis is a known complication of antivirals used to treat hepatitis B virus and HIV. Patients and methods: Measures were evaluated at baseline, week 4, end of treatment, and 12–24 weeks after treatment. Mixed-effects modeling was used to determine factors influencing glucose and lactate over time. Results: In total, 442 patients were treated (mean age 56, 65% male, 72% genotype 1, 48% cirrhotic). Glucose did not change on or after DAA treatment from baseline ( P =0.51) aside from those with untreated diabetes, which declined ( P =0.02). Overall, there was a decline in lactate following HCV treatment (mean 2.4–2.1 mmol/l; P <0.001). Lactate initially increased on treatment and then decreased after treatment completion in male patients treated with ribavirin. This pattern was not observed in other groups. There was no evidence of lactic acidosis with HCV nucleotide use. Conclusion: Distinct glucose and lactate trajectories were identified without evidence of DAA metabolic toxicity. HCV treatment does not improve random glucose levels aside from perhaps in untreated diabetic patients.